Science mapping for radiation shielding research - MEHMETCİK, HAKAN (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This article examines intellectual, conceptual, and social networks among academics, organizations, and countries, as well as quantifies the scientific production, assesses scientific quality and impacts in the field of radiation shielding. To this end, we use a bibliometric analysis to evaluate the radiation shielding publication record. The bibliographic search is carried out in the ISI Web of Science, and time span covers documents written from 2000 to 2020. Along with descriptive statistical tools, we utilize the R package Bibliometrix as a tool to perform bibliometric analysis in order to model networks among authors, articles, resources, references, keywords, institutions and countries. This investigation reveals substantial radiation shielding publishing trends, especially in terms of co-authorships, citations, institutional cooperation and author country of origin.
Keywords: Radiation shielding; Bibliometric analysis; Scientometrics; Citation analysis; MECHANICAL-PROPERTIES; BIBLIOMETRICS